Establishing a Pilot Interprofessional Education (IPE) Program in a Higher Education Institution (HEI) in the Philippines - Michael Sy; Roi Charles Pineda; Reeva Ann Sumulong; Annalyn Navarro (San Beda University, 2020)
A pilot interprofessional education (IPE) program in the Philippines has been initiated in a private higher education institution by three Filipinos who were formally trained in IPE from a World Health Organization (WHO) Collaborating Centre for Research and Training on IPE. Guided by the WHO educator and curricular mechanisms on IPE and an understanding of the local context, a four-stage action plan was created for the pilot IPE program, which involved 10 health science programs. The experience from the initial implementation was challenging and required perseverance as well as inclusive leadership. Nevertheless, the program's accomplishments such as continuous faculty training in IPE, constant communication among faculty members and students on IPE, and an inter-university collaboration to host the first-ever local IPE conference were noted. The article concludes with lessons learned from the pilot IPE program and future directions in further contributing to the growth and sustainability of IPE programs in the Philippines.